Antibacterial Test of Trembesi Leaf Extract (Samanea saman) on E-coli Bacteria - Ratrifah, Amruli Sella; Suproborini, Arum; Kusumawati, Desi (Universitas PGRI Madiun, 2026)
Trembesi plant (Samane saman (Jacq.) Merr) is a plant that has the potential as a traditional medicine. According to previous research, the trembesi plant is used by the community as a traditional medicinal plant. Bacillus cereus bacteria as gram positive is the most common cause of diarrhea and vomiting in humans. The purpose of this study was to test the antibacterial properties of trembesi leaf extract against Bacillus cereus. This study used a laboratory experimental method with extraction using the remaceration method with 96% ethanol solvent. Chloramphenicol was used as a positive control, while aquadestilata was used as a negative control. The concentrations used in this study were 10%, 15% and 20%. The results of the research were that the average diameter of the inhibition zone for Bacillus cereus bacteria at concentrations of 10%, 15% and 20% was 21.1 mm, 22.8 mm and 23.5 mm. The ethanol extract of trembesi leaves has antibacterial activity against Bacillus cereus bacteria.